Praktik Etis dalam Pemberdayaan Masyarakat: Studi Kasus Masyarakat Berbagi Nasi Kabupaten Tulungagung - Danang nugroho; Muhammad khoer saefullah; Filo fikri febian; Agung luthfi rama saputra; Betran aji pamungkas; Hikmal khalidd A; Silvia fitriana; Ahmad dinar syahrul ramadhan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research reviews the level of poverty in Indonesia as a complex global problem that requires joint attention from both developed and developing countries. Responding to the pressing problem of poverty, individuals who are aware of their social responsibility founded the Rice Sharing Community, which is a proactive approach to overcoming economic inequality. This research, located at the intersection of economic challenges and ethical considerations, contributes valuable insights into the complexities of poverty, while highlighting the emergence of community-based solutions such as Nasi Sharing Communities as an ethical response to community needs. This study shows that overcoming poverty requires a multifaceted approach, combining economic strategies with ethical considerations to promote community empowerment and social responsibility.